Association of laser therapy and acupuncture in the treatment of intervertebral disc disease in a canine: Case report (Research, Society and Development, 2024)
Intervertebral disc disease (IVDD) in dogs is a common condition in veterinary medicine that affects the spine and can lead to spinal cord compression. The intervertebral discs, whose purpose is to cushion shocks and allow mobility, can suffer degeneration, leading to protrusion or extrusion of the disc material and consequent spinal cord compression. Chondrodystrophic breeds, such as Dachshund and French Bulldog, are more predisposed. Clinical signs include pain, ataxia, and in severe cases, paralysis and loss of sensation. Diagnosis involves clinical history, physical and neurological examination and images such as magnetic resonance imaging or computed tomography. Treatment can be surgical or conservative. The objective of this study was to report the case of a French Bulldog dog, 2 years old and weighing 15 kg, diagnosed with IVDD, who opted for conservative treatment with laser therapy and acupuncture. These therapies aim to relieve pain, reduce inflammation, and stimulate tissue and sensory regeneration. After four months of weekly treatment, the dog showed significant improvement, reducing symptoms and maintaining stable mobility. This case exemplifies the effectiveness of conservative treatment through integrative medicine for IVDD, highlighting the importance of choosing therapies based on the animal's clinical status and the conditions of the owners.